(untitled) (Journal of the College of Education for Women, 2019)
The aim object of research is to show the computerized services library of Salahaldeen University in Erbil city in Iraq, so the research treatment all side of library such as building, location ,staff ,finance, resource collection and services ,we refer to. problem which face library such as administration and finance through the using Of case study method, reference source ,meeting , online comment and data record .The study focus develop in library departments, users services, management ,staff, the resource collection, building and location.The study ending with many results and recommendation to develop the library services by using modern Information system to all users inside and outside the university and link them with other modern communities.